2023
DOI: 10.1101/2023.09.21.558824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic divergence and genomic architecture at two different stages of speciation in a marine snail

Francesca Raffini,
Aurélien De Jode,
Kerstin Johannesson
et al.

Abstract: Speciation typically occurs in a time frame too long to be observed directly. This issue can be over-come by studying pairs of populations at different points in the speciation continuum, ideally within clades so that patterns are not confounded by differences among taxa. Such comparisons are possible in the marine snail Littorina saxatilis because it shows repeated occurrence of ecotypes adapted to either crab predation or wave action that differ in age and environmental context. Here, we explored transects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(207 reference statements)
0
1
0
Order By: Relevance
“…Across the species distribution, gene flow is occurring at different rates between the two ecotypes. In Sweden, allelic frequencies present a clinal pattern from crab to wave habitat (Westram et al 2021), while in Spain two distinct genetic clusters are found in upper and lower shore areas (Raffini et al 2023). This particular configuration enables the characterization of genomic, phenotypic, and organismal differences between pairs of populations from the same species at various stages of divergence, making L. saxatilis a most appropriate system to study the speciation process (Johannesson et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Across the species distribution, gene flow is occurring at different rates between the two ecotypes. In Sweden, allelic frequencies present a clinal pattern from crab to wave habitat (Westram et al 2021), while in Spain two distinct genetic clusters are found in upper and lower shore areas (Raffini et al 2023). This particular configuration enables the characterization of genomic, phenotypic, and organismal differences between pairs of populations from the same species at various stages of divergence, making L. saxatilis a most appropriate system to study the speciation process (Johannesson et al 2023).…”
Section: Introductionmentioning
confidence: 99%